(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study entitled Analysis of Changes in Rainfall Patterns in Rajshahi Division using GIS is an experimental climatological research. The main objectives of the study is to examine the long-term changes in rainfall patterns of Rajshahi Division. Secondary data of rainfall distribution have been collected from Bangladesh Meteorological Department (BMD), Dhaka. The study has analysed monthly, seasonal and annual rainfall distribution pattern from 1962 to 2007 of five selected weather stations namely Bogra, Dinajpur, Ishurdi, Rajshahi and Rangpur. For convenience of analysis, the data has been divided into two halves of time period as 1962-1984 and 1985-2007. Based on GIS, the study gifts the spatial analysis of rainfall patten using Thiessen Polygon Method, Isohytal and Hytograph Method and Percentage Method. It has been found that there is evidence of annual rainfall change with an increasing pattern in Bogra, Dinajpur, Rajshahi and Rangpur. In these four stations, the changing pattern in Rangpur is the highest. Downward shift of annual rainfall shows a decreasing pattern in Ishurdi. The descending order of monthly and seasonal rainfall pattern for Ishurdi, Rajshahi and Rangpur has been found as July > June > September >August > October > April > March > February > November > December. Although Bogra and Dinajpur have contained this trend in the same order from July to March, anomalies pattern has been found for last four months. The seasonal variation of rainfall has been established as Monsoon > Pre Monsoon > Post Monsoon > Winter for all those five stations. Evaluating the rainfall contour lines, it has been found that the rainfall annually varies from 1542.1 mm to 2235.8 mm in Rajshahi Division. The average number of rainy days in this region mostly varies from 86 to 112 days per year. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22223 J. Environ. Sci. & Natural Resources, 7(2): 141-149 2014